Microbial effects and home‐field advantage in holm oak (Quercus ilex) germination - Francisco I. Pugnaire; Elena Díaz‐Santiago; Miguel Hurtado‐Martínez; Christian Kindler; Esteban Manrique (Ecosphere, 2025)
Abstract Germination is a critical process influenced by multiple abiotic and biotic factors and depends on the interaction between microorganisms and the environment. As plants select specific sets of microbes that evolve together in response to local conditions, we looked at the role of microorganisms on holm oak (Quercus ilex) germination to test whether soil microbial communities enhanced germination of seeds from its own habitat more than soil communities from other habitats, in accordance with the home‐field advantage (HFA) hypothesis reported for litter decomposition. In a growth chamber experiment, we used sterilized seeds from two localities with contrasting environmental conditions sowed on a sterilized substrate, added inocula containing the microbiome extracted from the two soils with a factorial design, and recorded seed germination over two months. Fungi and bacteria extracted from Somiedo, the wet site, enhanced Q. ilex seed germination more than extracts from Ronda, the dry site, pointing to soil microbes as an important controlling factor. There was a significant difference in HFA between the two localities, being positive in Somiedo and negative in Ronda, suggesting that plant–soil coevolution was more difficult in harsher environment than in milder environment. Our results provide evidence of the critical role of soil microbial communities in Q. ilex germination.